2017
DOI: 10.1103/physreve.96.022301
|View full text |Cite
|
Sign up to set email alerts
|

Mutually cooperative epidemics on power-law networks

Abstract: The spread of an infectious disease can, in some cases, promote the propagation of other pathogens favoring violent outbreaks, which cause a discontinuous transition to an endemic state. The topology of the contact network plays a crucial role in these cooperative dynamics. We consider a susceptible-infected-removed-type model with two mutually cooperative pathogens: An individual already infected with one disease has an increased probability of getting infected by the other. We present a heterogeneous mean-fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 27 publications
4
42
0
Order By: Relevance
“…Only recently, cooperative contagion in which infection with one transmissible agent facilitates infection with another was investigated [36][37][38][39][40][41][42][43][44][45][46][47]. These studies mainly focused on transient dynamics of the generic susceptible-infected-recovery (SIR) model in which individuals acquire immunity after infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, cooperative contagion in which infection with one transmissible agent facilitates infection with another was investigated [36][37][38][39][40][41][42][43][44][45][46][47]. These studies mainly focused on transient dynamics of the generic susceptible-infected-recovery (SIR) model in which individuals acquire immunity after infection.…”
Section: Introductionmentioning
confidence: 99%
“…This model exhibits avalanche-like outbreak scenarios, depending on the level of cooperation and the structure of the underlying transmission network. Analytical insights [44] have been obtained that explain the role of network topology in cooperative bond percolation systems, in multiplex systems [45], power-law networks [43], as well as sequential coinfection on Poisson networks [37]. Furthermore, it has been found that highly clustered structures in population aid the proliferation of coinfections, contrary to the effect observed in single disease dynamics [41].…”
Section: Introductionmentioning
confidence: 99%
“…This leads to two possible solutions for ρ ab in the region above, but close to the epidemic threshold: if both diseases are not able to meet, ρ ab ≈ 0, while if they meet, ρ ab has a high value. In fact, finite system size effects may hide the broad jumps, appearing even in networks with broad degree distributions [32]. In our case, similar mechanisms, including the influence of the temporal connectivity pattern, explain how the cooperative interaction reinforces the upper endemic branch: infections spread together in the temporal clusters associated with high activity periods, while the night valley of activity and the stochastic recovery allow diseases to separate and spread independently, leading to macroscopic coinfection effects in ρ ab for the cases in which diseases meet again.…”
Section: Resultsmentioning
confidence: 99%
“…Well-known examples include the case * chenl@snnu.edu.cn of pneumonia bacterium like Streptococcus pneumoniae and viral respiratory illness (e.g., seasonal influenza) where they mutually facilitate each other's propogation [21,22], and the coinfection between human immunodeficiency virus and a host of other infections [23][24][25][26][27]. The interaction among different infections can be either competitive [28][29][30][31][32][33][34] (they suppress each other's circulation) or cooperative [35][36][37][38][39][40][41][42] (they support each other). The mean-field treatment and percolation studies of structured population reveal a rich spectrum of new dynamical features that are unexpected in the classic scenario of single infection.…”
Section: Introductionmentioning
confidence: 99%